Modelling approach in assessing and predicting the trajectory and spatial distribution of floating plastic debris in coastal water of East Coast Peninsular - Ramli, Muhammad Zahir (2021)
Marine debris issues have been one of the major problems that every nation is facing around the world Several studies have reported the accumulation of marine debris both in Peninsular and East of Malaysia in terms of its distribution on diff erent places, temporal and seasons eff ect and the major debris type found on Malaysian coastline. However, the study on route and trajectories of fl oating debris in Malaysia remains to be accomplished. A numerical approach could be a better view and improve our knowledge on the behaviour and fate of marine debris in our coastline. Particle tracking model was used to provide 1) the possible sources of fl oating marine debris, 2) the distribution of fl oating marine debris during diff erent seasons, and 3) the trajectory of marine debris released from our coastline. We use the Lagrangian ocean analysis tool, OceanParcels software as our main framework to simulate and model the particle integrated with ocean circulation model from the GOFS 3.1, a reanalysis ocean model by Hybrid Coordinate Ocean Model (HYCOM) and Navy Coordinate Ocean Model (NCODA). Particle tracking model and limited in-situ observation data shown a good agreement in terms of validation and results. Results illustrate several possible hotspots of accumulation and sources of fl oating marine debris along East Coast of Peninsular Malaysia.